To be or not to be – a data set. Art, technology and identity in the new informational order - F. Costa (EAI Endorsed Transactions on Creative Technologies, 2020)
In recent decades, a significant part of public and private governmental efforts has been devoted to developing technologies to collect and analyze data about living beings. On the one hand, data on their biological endowments, such as in biometrics or measurements of organic processes with biomedicine devices. On the other hand, data about their "forms of life": habits, opinions, even emotions, such as in data mining. Between "fingerprint" and "digital footprint", then, is stretched out one of the main lines of force of the techno-scientific intelligibility grid about what we are and what we could be. I will discuss three strategies with which some contemporary artists appropriate the new technologies for recording information from living bodies to unveil critically the mechanisms of capture of individuals and individuations they realize. In the end, I will resituate this question: what is at stake in the incitement to understand ourselves as a "data set"?